Incomplete Enforcement with Endogenous Regulatory Choice - Devon Garvie; Andrew Keeler (Queen's University, Department of Economics, 1993)
This paper extends the economics literature on the incomplete enforcement of social regulation by incorporating regulatory choice in an institutional environment of limited regulatory resources and powers. We show how regulatory decisions determine the structure of incentives faced by regulated firms. Our results indicate that the expense of monitoring relative to the regulator's power to levy penalties helps to explain the differences between "compliance" and "deterrence" enforcement styles. We find that in most circumstances firms with higher abatement costs will receive a larger share of regulatory resources and thus face higher penalties than firms with lower costs.
Keywords: 330